2003
DOI: 10.1097/00005237-200310000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pain From Heel Stick in Neonates

Abstract: The heel stick procedure is the most common painful procedure performed in preterm and full-term neonates. Various nonpharmacologic interventions have been used for pain relief. However, the magnitude of the effect of different interventions has received little attention. In this study, 4 eligible studies conducted in Thailand, focusing on the effects of interventions on pain responses to heel stick procedure in neonates, were obtained for analysis. Swaddling in full-term newborns was found to have the largest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Heel stick, which is used for diagnosis in newborn screening tests, is one of the most frequently performed interventions with newborns (da Motta & da Cunha, 2015; Morrow, Hidinger, & Faulk, 2010;Okan, Ozdil, Bulbul, Yapici, & Nuhoglu, 2010;Prasopkittikun & Tilokskulchai, 2003). At present, it is recommended to use pharmacologic and nonpharmacologic methods with invasive medical procedures in newborns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heel stick, which is used for diagnosis in newborn screening tests, is one of the most frequently performed interventions with newborns (da Motta & da Cunha, 2015; Morrow, Hidinger, & Faulk, 2010;Okan, Ozdil, Bulbul, Yapici, & Nuhoglu, 2010;Prasopkittikun & Tilokskulchai, 2003). At present, it is recommended to use pharmacologic and nonpharmacologic methods with invasive medical procedures in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014). Breastfeeding is reported as effective in reducing pain during minor painful procedures (Chromá & Sikorová, 2012;da Motta & da Cunha, 2015;Obeidat & Shuriquie, 2015;Shah et al, 2012), and it is suggested that it should be used to reduce pain during interventional procedures in newborns (Ali et al, 2016;Reece-Stremtan & Gray, 2016;Shah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Contact such as holding can reduce response to painful procedures [ 29 31 ]. Holding by the caregiver is recommended by the WHO for infants and young children receiving vaccine injection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, references cited in this article to justify the need for this clinical trial do not support the potential analgesic mechanism of upright or supine holding alone. 9,10 The authors did not mention an extensively cited Cochrane systematic review conducted by Riddell et al 11 on the effectiveness of rocking/ holding and other nonpharmacological analgesic strategies, which found low-quality evidence to suggest that holding alone is effective in reducing pain (ie, reactivity or regulation) in neonates. As highlighted by McNair et al, 12 holding should be considered only as an adjuvant intervention to other effective analgesic strategies such as offering small amounts of sweet solutions.…”
Section: Disclosurementioning
confidence: 99%